2022
DOI: 10.3390/atmos13111924
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Virtual Prediction of Vehicle-Related Particle Emissions and Their Influence on Ambient PM10 in an Urban Environment

Abstract: As a result of rising environmental awareness, vehicle-related emissions such as particulate matter are subject to increasing criticism. The air pollution in urban areas is especially linked to health risks. The connection between vehicle-related particle emissions and ambient air quality is highly complex. Therefore, a methodology is presented to evaluate the influence of different vehicle-related sources such as exhaust particles, brake wear and tire and road wear particles (TRWP) on ambient particulate matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the context of future environmental policy and the development of electric vehicles, the issue of non-exhaust emissions is becoming increasingly important. The problem of dust emissions from tires, brakes and road surfaces has been the subject of many papers [16][17][18][19][20][21][22][23][24][25][26]. In them, the authors focused on the problem of measuring dust emissions from these non-engine sources under laboratory and road conditions [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of future environmental policy and the development of electric vehicles, the issue of non-exhaust emissions is becoming increasingly important. The problem of dust emissions from tires, brakes and road surfaces has been the subject of many papers [16][17][18][19][20][21][22][23][24][25][26]. In them, the authors focused on the problem of measuring dust emissions from these non-engine sources under laboratory and road conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations: Modern technologies allow the modeling and simulation of brake pad dust emissions, which can contribute to a better understanding of the process and potential environmental impacts [21].…”
Section: Introductionmentioning
confidence: 99%
“…To study gas diffusion in soil caused by leakage accidents in urban buried natural gas pipelines, some researchers proposed suggestions for the proper utilization of soil near the pipelines by using fluid mechanics theory, porous media theory, and CFD models [7,8]. Using a CFD model, Feißel et al [9] examined how vehicle emissions affect air quality and suggested a simplified prediction method. Schalau et al [10] developed and validated a modified k-ε-turbulence model in OpenFOAM v5.0 for heavy gas dispersion in built-up areas under atmospheric conditions, and the result demonstrates that the model is reliable in prediction.…”
Section: Introductionmentioning
confidence: 99%